Graphene-based terahertz electronics and plasmonics : detector and emitter concepts - Mitin, V. V. (Vladimir Vasilʹevich); Ryzhii, Victor; Otsuji, Taiichi, 1959- (Singapore : Jenny Stanford Publishing, 2021)
Graphene demonstrates interesting electrical, optical, and optoelectronic properties. A number of other one-atom-thick material structures have been discovered and studied. Industrially applicable technologies for these structures are currently under active development. In spite of enormous research in the area of devices based on graphene, the number of extensive review publications on THz devices based on graphene is small. This review volume would fill the gap. Researchers and engineers working in the fields of electronics and plasmonics can use it to understand the influence of plasmonics on device performance. The book can be also be used as a required text for doctorate courses and as a supplementary material for postgraduate courses. The material presented in the book is reviewed in detail in Chapter 1. Chapter 2 discusses the electronic and plasmonic properties of graphene and heterostructures based on graphene for all devices. Chapters 3-7 focus on the concepts of detectors and emitters with a special emphasis on plasmonic enhancement of those devices as well as on population inversion and lasing.
1. Introduction 2. Electronic and Plasmonic Properties of Graphene and Graphene Structures 3. Detectors Based on Lateral Transport in Graphene and Graphene Structures 4. Population Inversion and Negative Conductivity in Graphene and Graphene Structures 5. Stimulated Emission and Lasing in Graphene and Graphene Structures 6. Detectors and Emitters Based on Photon/Plasmon-Assisted Tunneling between Graphene Layers 7. Graphene-Based van der Waals Heterostructures for THz Detectors and Emitters
OCLC-licensed vendor bibliographic record.
Keywords: Electromagnetic devices; Terahertz technology; Graphene; MEDICAL / Biotechnology; SCIENCE / Nanostructures; SCIENCE / Physics